Primary treatment of chronic pulmonary aspergillosis with weekly liposomal amphotericin B: A case report from Uganda - Winnie Kibone; Felix Bongomin; David W. Denning; David B. Meya (Medical Mycology Case Reports)
Chronic pulmonary aspergillosis (CPA) treatment in Africa remains unexplored. We present a 23-year-old Ugandan male, previously treated thrice for pulmonary tuberculosis, developing CPA. Imaging showed lung fibrosis, bronchiectasis, and a fungal ball. He received weekly 600mg (10mg/kg) of liposomal amphotericin B for six weeks, leading to marked clinical improvement. Weekly liposomal amphotericin B may be a viable treatment option for CPA in resource-limited settings.